Analysis of Physical-Chemical Parameters as One of Water Quality Stem Determinant in Palangki Sijunjung, West Sumatera - Gusmaweti Gusmaweti; Lisa Deswanti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this study was to analyze the physical and chemical parameters of waters Palangki Sijunjung Batang West Sumatra. Palangki rod is one of the river located in Palangki Sijunjung district, West Sumatra, which is used by residents as one for gold mining. Determination of sampling stations porpusive water sampling stations chosen three that are considered to represent perarian include: stasin I location (center of gold mining), the second station location (downstream part of the river) and the station III (upper part), each taken three bags station water samples at random. Further water samples taken to the laboratory for chemical analysis. The results showed that the outcome measure physical parameters such as: water temperature ranges between 25-26 ° C, the transparency of between 10-30 cm, humidity 60-65 g / m3, the color of the water was murky, and the current velocity ranging between 8-15 m / sec. Furthermore, chemical factors waters Trunk Palangki found that the average water pH 6, dissolved oxygen (DO) ranged from 5.25 to 5.96 mg / l and the quality standard of 5 mg / l, BOD ranges from 2.80 to 3, 49 mg / l and the quality standard of 3 mg / l, COD ranged from 47.05 to 78.25 mg / l and 25 MGL quality standards, total organic material (TOM) berkiar between 9.61 to 12.10 mg / l and mutu110 raw mg / l. as well as the levels of Mercury (Hg) 0.098 to 0.208 mg / l and quality standard of 0.002 mg / l. From the results of this study concluded that concentrations of mercury (Hg) in the water exceeds the threshold value means heavy metal contaminated.Keywords: Factor, physics, chemistry, perairan